1994
DOI: 10.1029/94gl01287
|View full text |Cite
|
Sign up to set email alerts
|

Ice nucleation in the upper troposphere: Sensitivity to aerosol number density, temperature, and cooling rate

Abstract: We have investigated the processes that control ice crystal nucleation in the upper troposphere using a numerical model. Nucleation of ice resulting from cooling was simulated for a range of aerosol number densities, initial temperatures, and cooling rates. In contrast to observations of stratus clouds, we find that the number of ice crystals that nucleate in cirrus is relatively insensitive to the number of aerosols present. The ice crystal size distribution at the end of the nucleation process is unaffected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
84
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 94 publications
(90 citation statements)
references
References 17 publications
6
84
0
Order By: Relevance
“…Thus the consumption of supersaturation proceeds slowly and the nucleation processes can act longer and at a higher rate, producing more crystals than in the warmer case. This effect has been observed earlier in simulations by Jensen and Toon (1994). Second, one observes that already the curve for SNF = 0.3 bears signs of homogeneous nucleation, such that in this case the critical soot concentration is one order of magnitude larger (i.e.…”
Section: The Box Modelsupporting
confidence: 59%
“…Thus the consumption of supersaturation proceeds slowly and the nucleation processes can act longer and at a higher rate, producing more crystals than in the warmer case. This effect has been observed earlier in simulations by Jensen and Toon (1994). Second, one observes that already the curve for SNF = 0.3 bears signs of homogeneous nucleation, such that in this case the critical soot concentration is one order of magnitude larger (i.e.…”
Section: The Box Modelsupporting
confidence: 59%
“…A number of modeling studies have shown that if ice nucleation occurs via homogeneous freezing, the resulting ice concentration is primarily controlled by cooling rate, with aerosol abundance having a minor effect (e.g., Jensen and Toon, 1994;Kärcher and Lohmann, 2002). At low temperatures and with moderate-to-rapid cooling rates, the ice concentration could become comparable to the concentration of aerosols available, in which case ice concentration could be controlled by aerosol abundance (Kay and Wood, 2008).…”
Section: Ttl Cirrus Microphysical Properties Predicted By Homogeneousmentioning
confidence: 99%
“…Depending on optical thickness and altitude, as well as on the albedo of the surface or lower clouds, the net effect on climate can either be a cooling or warming (Chen et al, 2000;Fusina et al, 2007;Corti and Peter, 2009), but quantifying the magnitude of this effect is difficult because of uncertainties in these or other quantities characterizing the cirrus life cycle (Lynch et al, 2002). Furthermore, microphysical properties such as number density, size and shape of the ice crystals affect the cloud lifetime and radiative properties and thus the humidity of the upper troposphere and lower stratosphere (Jensen and Toon, 1994).…”
Section: A Cirisan Et Al: Balloon-borne Match Measurementsmentioning
confidence: 99%